Clinical Aspects of Bacterial Corneal Ulcer Prolonged Course, the Role of Herpes Viruses in Its Pathogenesis, Treatment - V. V. Neroev; L. A. Katargina; L. A. Kovaleva; G. I. Krichevskaya; N. V. Balatskaya (Oftalʹmologiâ, 2019)
Purpose: to study the role of human herpesviruses (HHV) in the pathogenesis of prolonged bacterial corneal ulcers. Patients and methods. 117 patients with bacterial corneal ulcer were examined. Two groups were identified: a favorable course-with duration of bacterial corneal ulcer epithelialization for 17 days (62 people) and a prolonged course with a persistent ulcer more than 17 days (55 people). Blood samples (n = 117) and scrapes from corneal ulcer (n = 117) were investigated in polymerase chain reaction (PCR) for the presence of deoxyribonucleic acid (DNA) of Herpes simplex virus (HSV1, 2), Epstein-Barr virus (EBV), Human herpesvirus type 6, 7 (HHV-6, HSV-7). Results. The HSV1, 2 and EBV genomes were detected in the cornea significantly more often in BCU of prolonged course compared with a favorable course (HSV1, 2 p = 0.012; EBV p = 0.012), and HHV-6 was detected not only in the cornea (p = 0.000), but also and in blood (p = 0.007). In patients with HHV DNA in corneal scarps and/or blood, after resorption of purulent infiltrate, corneal epithelialization was absent, and the use of antiherpetic drugs allowed to reduce the completion time of BCU epithelialization. Conclusion. The role of HHV-6, EBV, HSV 1, 2 in the pathogenesis of bacterial corneal ulcer of protracted course was revealed. The expediency of examination of patients with bacterial corneal ulcer on HHV is shown, a method of treatment is proposed, including antiherpetic therapy, which makes it possible to prevent the development of a protracted course.